Method for coating single crystal type lithium nickel cobalt manganese oxide positive electrode material with V-Sm

Surface modification of single crystal lithium nickel cobalt manganate cathode material through V-Sm double coating technology solves the problems of hindered lithium ion diffusion and structural change of single crystal lithium nickel cobalt manganate cathode material during charge and discharge. , achieving the effect of improving battery charge and discharge capacity, Coulomb efficiency and structural stability.

CN119361652AActive Publication Date: 2025-01-24JIANGSU UNIV OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411552321.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-01-24
Estimated Expiration
2044-11-01

Smart Images

  • Figure CN119361652A_ABST
    Figure CN119361652A_ABST
Patent Text Reader

Abstract

The invention relates to a method for coating a single crystal type nickel cobalt lithium manganate positive electrode material with V-Sm, and belongs to the technical field of battery positive electrode material synthesis, and the method comprises the following steps: S1, adding the single crystal type nickel cobalt lithium manganate positive electrode material into an ethanol solution, and violently stirring to obtain a suspension I; s2, taking a vanadium solution and a samarium solution, sequentially dropwise adding the vanadium solution and the samarium solution into the suspension I prepared in the step S1, and violently stirring for 30-40 minutes to obtain a suspension II; and S3, carrying out centrifugal separation on the suspension II prepared in the step S2, collecting a solid product, washing with an ethanol solution, carrying out vacuum drying, and calcining in an O2 atmosphere to obtain the V-Sm coated single crystal type lithium nickel cobalt manganate positive electrode material. According to the V-Sm coated single crystal type lithium nickel cobalt manganese oxide positive electrode material prepared by the invention, the electrochemical performance and the structural stability of the positive electrode material are greatly improved, and the service life is further prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of battery positive electrode material synthesis, and in particular to a method for V-Sm coating single crystal lithium nickel cobalt manganese oxide positive electrode material. Background Art

[0002] The single-crystal nickel cobalt manganese oxide positive electrode material is composed of unique micron-sized particles and has high mechanical strength. During the rolling process of the pole piece, the material breakage rate is low. At the same time, during the charge and discharge cycle, intercrystalline cracks are not easy to appear, and it has better cycle stability. Therefore, the single-crystal nickel cobalt manganese oxide positive electrode material is expected to replace the traditional polycrystalline nickel cobalt manganese oxide positive electrode material to a certain extent.

[0003] Due to the relatively small size of single crystal particles, the high specific surface area will increase the side reactions of the electrode-electrolyte. In the absence of proper surface modification, single crystal particles are prone to direct interaction with the electrolyte, causing a series of interfacial problems. For example, the corrosive hydrofluoric acid (HF) produced during the decomposition of the electrolyte will react adversely with the cathode material, and the thick surface film formed may hinder the diffusion of lithium ions, thereby causing an increase in the internal resistance of the battery. After long-term charging and discharging, due to the continuous loss of lithium ions, the structure of the cathode material may change from a layered structure to a spinel structure or even a rock salt phase structure. The above changes will further affect the electrochemical properties of the material.

[0004] The existing technology generally adopts the method of doping and coating to modify the single-crystal lithium nickel cobalt manganese oxide positive electrode material. The purpose of doping is to stabilize the crystal structure and reduce the Li + and Ni 2+ Mixing, improving electronic conductivity, and strengthening the chemical bonds between transition metals to inhibit oxygen release; in addition, by introducing ions with larger radius to adjust the interlayer distance, Li + Shuttle is more convenient. The purpose of coating is to construct a protective film on the surface of single-crystal nickel cobalt lithium manganese oxide positive electrode material particles to isolate the material from direct contact with the electrolyte, thereby reducing the chance of side reactions; in addition, the coating layer serves as a channel for high-speed diffusion of lithium ions and promotes lithium ion migration. However, the coating material is difficult to maintain its shape during the electrochemical cycle, and even has a certain impact on the rate performance. In response to the above-mentioned technical problems, the inventors provide a new preparation process for single-crystal nickel cobalt lithium manganese oxide positive electrode material for lithium batteries. Summary of the invention

[0005] The object of the present invention is to provide a method for V-Sm coating single crystal lithium nickel cobalt manganese oxide positive electrode material, taking single crystal lithium nickel cobalt manganese oxide positive electrode material as the main body, performing surface V-Sm double coating modification on the single crystal lithium nickel cobalt manganese oxide positive electrode material, and improving the electrochemical performance and structural stability of the single crystal lithium nickel cobalt manganese oxide positive electrode material.

[0006] The present invention provides a method for V-Sm coating a single crystal lithium nickel cobalt manganese oxide positive electrode material, which adopts the following technical solution: A method for V-Sm coating a single crystal lithium nickel cobalt manganese oxide positive electrode material, comprising the following steps: S1. Adding a single crystal lithium nickel cobalt manganese oxide positive electrode material into an ethanol solution and stirring vigorously to obtain a suspension 1; S2, taking a vanadium solution and a samarium solution and sequentially adding them dropwise to the suspension 1 obtained in step S1, and vigorously stirring for 30-40 minutes to obtain a suspension 2; S3, centrifugally separating the suspension 2 obtained in step S2, collecting the solid product, washing it with an ethanol solution, vacuum drying it, and calcining it under an O2 atmosphere to obtain a V-Sm-coated single-crystalline lithium nickel cobalt manganese oxide positive electrode material.

[0007] Preferably, the mass concentration of the single crystal lithium nickel cobalt manganese oxide positive electrode material in the suspension 1 of step S1 is 30-100 mg / mL.

[0008] Preferably, the mass concentration of VCl3 in the vanadium solution in step S2 is 1-3 mg / mL; The vanadium solution in step S2 is prepared by reacting VCl3 with an ethanol solution.

[0009] Preferably, the mass concentration of Sm(NO3)3•6H2O in the samarium solution of step S2 is 1-4 mg / mL; The samarium solution in step S2 is prepared by reacting Sm(NO3)3·6H2O with an ethanol solution.

[0010] Preferably, the mass ratio of VCl3 and Sm(NO3)3·6H2O in the second suspension in step S2 is (1-2.5):(1-3).

[0011] Preferably, the stirring speed in step S1 and step S2 is 500-1000 rpm; The stirring time in step S1 and step S2 is 30-60 min.

[0012] Preferably, the mass percentage of V and Sm in the single crystal lithium nickel cobalt manganese oxide positive electrode material in step S3 is 1-5wt%.

[0013] Preferably, the vacuum drying temperature in step S3 is 70-100° C., and the vacuum drying time is 6-15 h; In step S3, the calcination temperature is 400-600° C., and the calcination time is 3-6 hours.

[0014] On the other hand, the present invention also provides a single-crystal nickel cobalt manganese oxide positive electrode material obtained by adopting the above-mentioned method of V-Sm coating single-crystal nickel cobalt manganese oxide positive electrode material.

[0015] Furthermore, the present invention also provides the use of the single-crystal nickel cobalt manganese oxide positive electrode material in the preparation of a lithium battery. In summary, the present invention includes the following beneficial technical effects: 1. The present invention effectively reduces the Li + / Ni 2+ The mixing degree of Li + The diffusion rate of Li + The transmission during the charge and discharge process is smoother, thereby improving the charge and discharge capacity and Coulomb efficiency of the battery; the V-Sm coating forms a uniform amorphous coating on the surface of the single-crystal nickel cobalt manganese oxide positive electrode material. The amorphous coating can effectively avoid direct contact between the positive electrode material and the electrolyte, preventing the corrosion and damage of the positive electrode material by the electrolyte, thereby improving the structural stability of the material. The V-Sm coating can also prevent attacks by harmful substances such as HF, further extending the service life of the battery.

[0016] 2. In the cycle performance test, the V-Sm coated and modified single-crystal nickel cobalt manganese oxide positive electrode material prepared by the present invention has significantly reduced polarization phenomenon, showing higher cycle stability. The presence of the V-Sm coating layer not only reduces the side reactions between the electrolyte and the electrode, but also inhibits the unstable growth of the SEI film, thereby reducing the damage to the particle surface structure; in addition, in the performance tests at different rates, the V-Sm coated and modified single-crystal nickel cobalt manganese oxide positive electrode material exhibits excellent rate performance. Especially at high current density, due to the coating layer on Li + The positive effect of migration enables the material to maintain a high discharge specific capacity at high rates. At the same time, after the current density is restored, the discharge specific capacity of the material can also be quickly restored, showing good reversibility. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 It is the XRD diffraction pattern of Examples 1-3 of the present invention and Comparative Example 1.

[0018] Figure 2 : is the XPS scanning spectrum of the product in the embodiment of the present invention, wherein a is the XPS total scanning diagram of the embodiment of the present invention, b is the Ni 2p fine energy spectrum, c is the V 2p fine spectrum; d is the Sm 3d fine spectrum.

[0019] Figure 31 and 2 are high-resolution transmission electron micrographs of embodiments of the present invention, wherein a, b and c are electron micrographs of NCM, and d, e and f are electron micrographs of NCM-2.

[0020] Figure 4 : It is an electrochemical performance curve diagram of an embodiment of the present invention, wherein a is the first cycle capacity-voltage curve of NCM, NCM-1, NCM-2 and NCM-3 in the voltage range of 2.75-4.3V, at 25°C, and under the condition of 0.1C (1C=160mAh•g-1); b is the cycle curve of NCM, NCM-1, NCM-2 and NCM-3 in the voltage range of 2.75-4.3V, at 25°C, and under the condition of 1C (1C=160mAh•g-1); c is the rate performance test of NCM, NCM-1, NCM-2 and NCM-3 in the voltage range of 2.75-4.3V and 25°C; d is a curve diagram of the average discharge capacity retention rate of NCM, NCM-1, NCM-2 and NCM-3. DETAILED DESCRIPTION

[0021] The following is combined with the embodiments and the attached Figure 1-4 The present invention is described in further detail.

[0022] Example 1 This embodiment provides a method for coating a single-crystal nickel-cobalt-manganese-oxide lithium positive electrode material with V-Sm, comprising the following steps: S1. Add 1 g of single-crystal nickel cobalt manganese oxide positive electrode material into 20 mL of ethanol solution at room temperature, and stir vigorously at a stirring speed of 500-1000 rpm for 30-60 min to obtain a suspension 1. S2, dissolving 17 mg VCl3 in 10 mL ethanol to prepare a vanadium solution, dissolving 18.02 mg Sm(NO3)3·6H2O in 10 mL ethanol to prepare a samarium solution, and dropping the vanadium solution and the samarium solution into the suspension 1 prepared in step S1 at a rate of 20-60 drops / min, and continuously stirring, controlling the stirring speed to 500-1000 rpm, stirring for 30-60 min, to obtain a suspension 2; S3. Centrifuge the suspension obtained in step S2, collect the solid product, wash it with ethanol solution, vacuum dry it at 80°C for 12h, take it out, and calcine it in O2 atmosphere for 3h, the calcination temperature is 3g, and obtain V-Sm coated single crystal lithium nickel cobalt manganese oxide positive electrode material, marked as NCM-2.

[0023] Example 2 The present embodiment provides a method for V-Sm-coated single-crystal nickel cobalt manganese oxide positive electrode material. The difference from Example 1 is that in step S2, 28 mg of VCl3 is dissolved in 10 mL of ethanol to prepare a vanadium solution, and 12 mg of Sm(NO3)3·6H2O is dissolved in 10 mL of ethanol to prepare a samarium solution. The vanadium solution and the samarium solution are sequentially added dropwise to the suspension one prepared in step S1 at a rate of 20-60 drops / min, and continuously stirred at a stirring speed of 500-1000 rpm and stirred for 30-60 min to obtain a suspension two; the V-Sm-coated single-crystal nickel cobalt manganese oxide positive electrode material obtained in step S3 is marked as NCM-1, and the remaining steps are the same as in Example 1.

[0024] Example 3 The present embodiment provides a method for V-Sm-coated single-crystal nickel cobalt manganese oxide positive electrode material. The difference from Example 1 is that in step S2, 13 mg of VCl3 is dissolved in 10 mL of ethanol to prepare a vanadium solution, and 37 mg of Sm(NO3)3·6H2O is dissolved in 10 mL of ethanol to prepare a samarium solution. The vanadium solution and the samarium solution are sequentially added dropwise to the suspension one prepared in step S1 at a rate of 20-60 drops / min, and continuously stirred. The stirring speed is controlled to 500-1000 rpm and stirred for 30-60 min to obtain a suspension two. The V-Sm-coated single-crystal nickel cobalt manganese oxide positive electrode material obtained in step S3 is marked as NCM-3, and the remaining steps are the same as in Example 1.

[0025] Comparative Example 1 This comparative example is a single-crystal nickel cobalt manganese oxide positive electrode material that has not been subjected to V-Sm coating treatment, marked as NCM.

[0026] Comparative Example 2 This comparative example provides a method for V-Sm coating a single crystal lithium nickel cobalt manganese oxide positive electrode material. The difference from Example 1 is that in step S2, 17 mg of VCl3 is dissolved in 10 mL of ethanol to prepare a vanadium solution, and the vanadium solution is added dropwise to the suspension one prepared in step S1 at a rate of 20-60 drops / min, and stirred continuously. The stirring speed is controlled to 500-1000 rpm and stirred for 30-60 min to obtain a suspension two. The remaining steps are the same as in Example 1.

[0027] Comparative Example 3 This comparative example provides a method for V-Sm coating a single crystal nickel cobalt manganese oxide lithium positive electrode material. The difference from Example 1 is that in step S2, 18.02 mg Sm(NO3)3·6H2O is dissolved in 10 mL ethanol to prepare a samarium solution, and the samarium solution is added dropwise to the suspension one prepared in step S1 at a rate of 20-60 drops / min, and stirred continuously. The stirring speed is controlled to 500-1000 rpm and stirred for 30-60 min to obtain a suspension two. The remaining steps are the same as in Example 1.

[0028] Comparative Example 4 This comparative example provides a method for V-Sm coating single crystal nickel cobalt manganese oxide positive electrode material. The difference from Example 1 is that in step S2, 5 mg of VCl3 is dissolved in 10 mL of ethanol to prepare a vanadium solution, and 5 mg of Sm(NO3)3·6H2O is dissolved in 10 mL of ethanol to prepare a samarium solution. The vanadium solution and the samarium solution are sequentially added dropwise to the suspension one prepared in step S1 at a rate of 20-60 drops / min, and continuously stirred at a stirring speed of 500-1000 rpm and stirred for 30-60 min to obtain a suspension two, wherein the mass ratio of VCl3 to Sm(NO3)3·6H2O is 1:1, and the remaining steps are the same as in Example 1.

[0029] Comparative Example 5 This comparative example provides a method for V-Sm coating single crystal nickel cobalt manganese oxide positive electrode material. The difference from Example 1 is that in step S2, 50 mg of VCl3 is dissolved in 10 mL of ethanol to prepare a vanadium solution, and 50 mg of Sm(NO3)3·6H2O is dissolved in 10 mL of ethanol to prepare a samarium solution. The vanadium solution and the samarium solution are sequentially added dropwise to the suspension one prepared in step S1 at a rate of 20-60 drops / min, and continuously stirred at a stirring speed of 500-1000 rpm and stirred for 30-60 min to obtain a suspension two, wherein the mass ratio of VCl3 to Sm(NO3)3·6H2O is 1:1, and the remaining steps are the same as in Example 1.

[0030] Comparative Example 6 This comparative example provides a method for V-Sm coating a single crystal nickel cobalt manganese oxide positive electrode material. The difference from Example 1 is that in step S2, 30 mg of VCl3 is dissolved in 10 mL of ethanol to prepare a vanadium solution, and 1 mg of Sm(NO3)3·6H2O is dissolved in 10 mL of ethanol to prepare a samarium solution. The vanadium solution and the samarium solution are sequentially added dropwise to the suspension one prepared in step S1 at a rate of 20-60 drops / min, and continuously stirred at a stirring speed of 500-1000 rpm and stirred for 30-60 min to obtain a suspension two, wherein the mass ratio of VCl3 to Sm(NO3)3·6H2O is 30:1, and the remaining steps are the same as in Example 1.

[0031] Comparative Example 7 This comparative example provides a method for coating a single-crystal nickel-cobalt-manganese-oxide lithium positive electrode material with V-Sm, comprising the following steps: S1. Add 0.5 g of single-crystal nickel cobalt manganese oxide positive electrode material into 20 mL of ethanol solution at room temperature, and stir vigorously at a stirring speed of 500-1000 rpm for 30-60 min to obtain a suspension 1. S2, take 20 mg VCl3 and dissolve it in 10 mL ethanol to prepare a vanadium solution, take 20 mg Sm (NO3) 3 · 6H2O and dissolve it in 10 mL ethanol to prepare a samarium solution, and add the vanadium solution and the samarium solution to the suspension one prepared in step S1 at a rate of 20-60 drops / min, and continue stirring, control the stirring speed to 500-1000 rpm, and stir for 30-60 minutes to obtain a suspension two, wherein the mass ratio of VCl3 to Sm (NO3) 3 · 6H2O is 1:1; S3. Centrifuge the suspension obtained in step S2, collect the solid product, wash it with ethanol solution, vacuum dry it at 80°C for 12h, take it out, and calcine it in O2 atmosphere for 3h, the calcination temperature is 3g, and obtain V-Sm coated single crystal lithium nickel cobalt manganese oxide positive electrode material 1.

[0032] Comparative Example 8 This comparative example provides a method for V-Sm coating a single-crystal nickel cobalt manganese oxide positive electrode material. The difference from comparative example 7 is that in step S1, 2 g of single-crystal nickel cobalt manganese oxide positive electrode material is added to 20 mL of ethanol solution at room temperature and vigorously stirred. The stirring speed is controlled to 500-1000 rpm and stirred for 30-60 min to obtain a suspension 1. The remaining steps are the same as those in Example 1.

[0033] Performance testing According to the methods of Examples 1-3 and Comparative Examples 1-8, single-crystal nickel cobalt manganese oxide positive electrode materials were prepared and cured, respectively, and mixed with conductive carbon black and polyvinylidene fluoride at a mass ratio of 8:1:1, and N-methyl pyrrolidone was added and stirred for 6 hours. The obtained mixed slurry was evenly coated on aluminum foil, placed in an oven at 110°C for 12 hours, and then cut into 12mm round electrode pieces. At 25°C, the charge / discharge rate was 1C at 2.75-4.3V (1C = 160mAh•g -1 ), the button-type batteries made of the single crystal nickel cobalt manganese oxide positive electrode materials prepared by Examples 1-3 and Comparative Examples 1-8 were subjected to cycle performance tests, and the capacity retention rate after 450 cycles was calculated, and the formula was as follows: capacity retention rate = 450th discharge specific capacity / first discharge specific capacity * 100%. The test results are shown in Table 1.

[0034]

[0035] It can be seen from the test data in Table 1 that the single-crystal nickel cobalt manganese oxide positive electrode materials prepared in Examples 1-3 of the present application all have good capacity retention rates.

[0036] Reference Figure 1 From the XRD diffraction pattern, it can be seen that all samples belong to the hexagonal α-NaFeO2 structure of the R-3m space group, and the sharp diffraction peaks indicate that they have a high degree of crystallinity; there are no impurity peaks in the XRD spectrum, indicating that the V-Sm coating has no effect on the lattice structure of the positive electrode material.

[0037] Reference Figure 2 , a shows the XPS total scan spectrum of NCM-2, from which elements such as nickel (Ni), cobalt (Co), manganese (Mn), oxygen (O), samarium (Sm) and vanadium (V) can be clearly detected.

[0038] Reference Figure 2 , b is the Ni 2p fine energy spectrum of NCM and NCM-2. It can be observed that the spectrum of Ni 2p is divided into two peaks, corresponding to Ni 2p 1 / 2 and Ni 2p 3 / 2 There are two energy level orbitals, both around 871eV and 854eV, where Ni 2p 3 / 2 Split into two peaks, corresponding to Ni 2+ and Ni 3+ , and through fitting analysis, it can be seen that Ni in NCM-2 2+ The proportion has decreased.

[0039] Reference Figure 2 , c is the V 2p fine spectrum, the peak at 513.2 eV represents V0. Due to the spin-orbit coupling effect, V 2p is divided into V 2p1 / 2 and V 2p 3 / 2 Two sub-levels. In V 2p 3 / 2 In the analysis of the sub-energy levels, three different peaks were detected, corresponding to different valence states of vanadium. Specifically, the peak at 516.1 eV corresponds to +3 valence vanadium (V 3 + ), while at 516.95eV and 517.45eV, they correspond to +4 valence (V 4+ ) and +5 (V 5+ ) of vanadium.

[0040] Reference Figure 2 , d is the Sm 3d fine spectrum, and we can see that there is Sm at 1083.2 eV 3+ The diffraction peak further proves that V-Sm has been successfully coated on the surface of the single crystal of single-crystalline lithium cobalt oxide positive electrode material.

[0041] Reference Figure 3 , a, b and c are electron microscope images of NCM, from which it can be seen that the surface of the material is smooth and the lattice fringes of about 0.4738 nm can be clearly identified, which is consistent with the crystal plane of the hexagonal α-NaFeO2 structure and has typical layered structural characteristics.

[0042] Reference Figure 3 , d, e and f are electron microscope images of NCM-2. The surface of the single-crystal lithium nickel cobalt manganese oxide particles is covered with a film, indicating that the V-Sm coating has been formed. After magnification, a relatively uniform amorphous coating with a thickness of about 1-3nm can be observed. The amorphous coating is beneficial to isolate the direct contact between the positive electrode material and the electrolyte, thereby improving the structural stability of the material and is expected to enhance the cycle performance of the battery. Moreover, lattice fringes with a spacing of about 0.4745nm can be clearly observed under the coating, which also corresponds to the LiNiO2 crystal plane with a hexagonal layered structure, indicating that the structure of the material is not affected.

[0043] Reference Figure 4 , a is the voltage range of 2.75-4.3V for NCM, NCM-1, NCM-2 and NCM-3, at 25℃, 0.1C (1C=160mAh·g -1 The initial discharge specific capacities of NCM, NCM-1, NCM-2, and NCM-3 are 121.8 mAh g -1 、123.8mAh·g -1 、149.7mAh·g -1 、139.6mAh·g -1, and the corresponding coulombic efficiencies were 84.3%, 84.4%, 87.2%, and 86.5%, respectively. The discharge specific capacity of NCM-1 has hardly changed compared with that of NCM, which may be due to insufficient coating and failure to form a complete coating layer. However, overall, the single crystal materials modified by V-Sm coating showed higher discharge capacity and coulombic efficiency, especially NCM-2, which showed the best charge and discharge performance. This may be because the V-Sm coating layer effectively inhibits the Li + / Ni 2+ Mixing reduces the irreversible capacity loss of materials.

[0044] Reference Figure 4 , b is NCM, NCM-1, NCM-2 and NCM-3 in the voltage range of 2.75-4.3V, 1C (1C = 160mAh g -1 ), the cycle curves at 25°C, the initial discharge specific capacities of NCM, NCM-1, NCM-2 and NCM-3 are 116.7 mAh·g -1 、111.1mAh·g -1 、115.3mAh·g -1 、111.6mAh·g -1 After 450 cycles, the discharge specific capacities of NCM, NCM-1, NCM-2, and NCM-3 were 94.7 mAh g -1 、93mAh·g -1 、99.7mAh·g -1 、94.7mAh·g -1 , and the corresponding capacity retention rates are 81.1%, 83.7%, 86.5% and 84.9% respectively. Among them, NCM-2 has the best cycle stability and the highest discharge specific capacity. This excellent cycle performance is due to the uniformly distributed V-Sm coating on the surface of the particles, which is conducive to the diffusion of lithium ions and prevents the side reactions caused by direct contact between the electrolyte and the electrode, thereby reducing the damage to the particle structure.

[0045] Reference Figure 4 , c shows the rate performance test of NCM, NCM-1, NCM-2 and NCM-3 at a voltage range of 2.75-4.3V and 25°C. The current density (i.e., rate) tested was 0.1C, 0.2C, 0.5C, 1C, 2C and 5C, respectively. Figure 4 It can be observed in Figure c that when the current density increases from 0.1C to 5C, the discharge capacity of the battery shows a gradual downward trend. The reason for this phenomenon is that at high current density, lithium ions (Li +) diffusion rate weakened, resulting in a decrease in discharge specific capacity. However, after the current density returned to 0.1C, the specific capacity recovered. Among them, NCM-2 maintained a high discharge specific capacity at all rates. The discharge specific capacity of NCM-3 decreased at the same current density, which may be because the excessive coating hindered the Li + In addition, when the current density was changed to 0.1C, the discharge capacity of NCM and NCM-2 samples recovered to 127.28 mAh g -1 and 132.7 mAh g -1 .

[0046] Reference Figure 4 , d shows that the average discharge capacity retention rate of NCM-2 is higher than that of NCM. This result clearly shows that the V-Sm coating plays a positive role in promoting the diffusion of lithium ions, thereby improving the rate performance of the modified samples. The improvement in cycle and rate performance is mainly due to the fact that the V-Sm coating can maintain a good ion conduction channel, reduce the interface impedance between the electrode material and the electrolyte, and ensure the performance stability of the battery during rapid charge and discharge.

[0047] The above are all preferred embodiments of the present invention, and are not intended to limit the protection scope of the present invention. Therefore, any equivalent changes made based on the structure, shape, and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for coating single-crystal nickel-cobalt-manganese-oxide lithium positive electrode material with V-Sm, characterized in that: The steps include: S1. Adding a single crystal lithium nickel cobalt manganese oxide positive electrode material into an ethanol solution and stirring vigorously to obtain a suspension 1; S2, taking a vanadium solution and a samarium solution and sequentially adding them dropwise to the suspension 1 obtained in step S1, and vigorously stirring for 30-40 minutes to obtain a suspension 2; S3, centrifugally separating the suspension 2 obtained in step S2, collecting the solid product, washing it with an ethanol solution, vacuum drying it, and calcining it under an O2 atmosphere to obtain a V-Sm-coated single-crystalline lithium nickel cobalt manganese oxide positive electrode material.

2. The method for V-Sm coating single crystal lithium nickel cobalt manganese oxide positive electrode material according to claim 1, characterized in that: The mass concentration of the single crystal lithium nickel cobalt manganese oxide positive electrode material in the suspension 1 of step S1 is 30-100 mg / mL.

3. The method for V-Sm coating single crystal lithium nickel cobalt manganese oxide positive electrode material according to claim 1, characterized in that: The mass concentration of VCl3 in the vanadium solution of step S2 is 1-3 mg / mL; The vanadium solution in step S2 is prepared by reacting VCl3 with an ethanol solution.

4. The method for V-Sm coating single crystal lithium nickel cobalt manganese oxide positive electrode material according to claim 1, characterized in that: The mass concentration of Sm(NO3)3•6H2O in the samarium solution of step S2 is 1-4 mg / mL; The samarium solution in step S2 is prepared by reacting Sm(NO3)3·6H2O with an ethanol solution.

5. The method for V-Sm coating single crystal lithium nickel cobalt manganese oxide positive electrode material according to claim 1, characterized in that: The mass ratio of VCl3 and Sm(NO3)3·6H2O in the second suspension in step S2 is (1-2.5):(1-3).

6. The method for V-Sm coating single crystal lithium nickel cobalt manganese oxide positive electrode material according to claim 1, characterized in that: The stirring speed in step S1 and step S2 is 500-1000 rpm; The stirring time in step S1 and step S2 is 30-60 min.

7. The method for V-Sm coating single crystal lithium nickel cobalt manganese oxide positive electrode material according to claim 1, characterized in that: The mass percentage of V and Sm in the single crystal lithium nickel cobalt manganese oxide positive electrode material in step S3 is 1-5wt%.

8. The method for V-Sm coating single crystal lithium nickel cobalt manganese oxide positive electrode material according to claim 1, characterized in that: In step S3, the vacuum drying temperature is 70-100° C., and the vacuum drying time is 6-15 hours; In step S3, the calcination temperature is 400-600° C., and the calcination time is 3-6 hours.

9. A single-crystal lithium nickel cobalt manganese oxide positive electrode material obtained by the method for coating a single-crystal lithium nickel cobalt manganese oxide positive electrode material with V-Sm according to claim 1.

10. Use of the single crystal lithium nickel cobalt manganese oxide positive electrode material according to claim 9 in the preparation of lithium batteries.

Citation Information

Patent Citations

  • Nickel-cobalt lithium manganate positive material, preparation method thereof and lithium ion battery

    CN108878859A

  • Organic matter coated multi-element positive electrode material, preparation method and application thereof, and lithium ion battery

    CN114695852A

  • Vanadium boride coated nickel cobalt lithium manganate positive electrode material and preparation method thereof

    CN114975907A

  • Positive electrode material, preparation method thereof and lithium ion battery

    CN117542987A